Conscience at war : the Israeli soldier as a moral critic - Linn, Ruth. (Albany : State University of New York Press, 1996)
A psychological study of the Intifada "refusers," focusing on the intellectual and moral challenges selective conscientious objection poses for resisters in Israel. Linn (School of Education, Haifa U.) uses the theories of Rawls, Walzer, Kohlberg, and Gilligan as a framework for understanding and interpreting interviews with objecting soldiers. Annotation copyright by Book News, Inc., Portland, OR.
Includes bibliographical references (pages 227-238) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Israel. -- Tseva haganah le-Yiśraʼel.; Israel. -- Tseva haganah le-Yiśraʼel; Conscientious objectors -- Israel; Israel -- Armed Forces; Objecteurs de conscience -- Israël.; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Armed Forces; Conscientious objectors; Israel